Engineering the Strategic Mind : A study of Demolition and Construction Strategies (Tikrit Journal For Political Science, 2024)
The strategic mind is the basis for the organization, stability, continuity and advancement of any society in the world, and the basis for a network of diverse relationships. But in light of its complete exposure to the flowing, deconstructive and destructive attempts represented by external threats (the information revolution, technological development, and the Internet) and influential ideologies aimed at taking away its ability to contemplate and think, then a conviction prevailed of the necessity for this mind to return to its firm decision, by searching for approaches to integration within Programs, initiatives or activities, and coming up with a purposeful and constructive strategy to rid the mind of deviant thoughts, cordoning off those effects, and pushing the nation towards stability, capacity building, and the acquisition of intergenerational skills, ultimately aiming to create and build the strategic mind, and enable it to reproduce awareness in terms of the ability to analyze and see. Reality and its understanding, synthesis, long-term visions, and building high perceptions to anticipate the future and strive to possess the tools to create it.
Keywords: The Strategic Mind, Demolition and Construction Strategies